PENGEMBANGAN STRATEGI MANAJEMEN PENGETAHUAN UNTUK MENDUKUNG PELAKSANAAN REFORMASI BIROKRASI: SEBUAH STUDI KASUS DI KEMENTERIAN PERINDUSTRIAN - Nurzaitun Purwasih; Dana Indra Sensuse (Jurnal Sistem Informasi, 2014)
Abstract Bureaucratic reform program is a bureaucratic change efforts towards the expected profile. One of program bureaucratic reform support is a knowledge management. Ministry of Industry (Ministry of Industry) as a driver and builder of national industry needs to change and improve bureaucracy so as to improve the ability of the industry sector in the face of global competition. Along with its efforts to implement bureaucratic reform, the Ministry of Industry has the implementation of knowledge management initiatives, but does not yet have a comprehensive knowledge management strategy. Ministry of Industry focus is on improving the quality of public services, one of which is supported by the development of e-government. ¬ the development process of e-government involves a variety of knowledge are scattered in various locations, both inside and outside the organization. This study seeks to formulate the knowledge management strategy with a focus on the development of e-government targets in order to reform the bureaucracy. The formulation of the strategy is done by using a knowledge strategy framework Zack. Strategies are formulated as follows: Ministry of Industry need to document work experiences into written form; Kemenperin need to increase the awareness of employees to share knowledge; Ministry of Industry needs to improve coordination and cooperation within the framework of knowledge management, both internal and inter-working unit with external parties; Ministry of Industry needs to facilitate storage and distribution of IT-based knowledge that can be reached easily by all employees of the Ministry of Industry; and the Ministry of Industry should establish management commitment to support the implementation of knowledge management.